Effects of sago starch on body weight, food intake, caecum short chain fatty acids, adipose tissue, and hepatic lipid content of fat-induced Sprague Dawley rats - Thompson, M. S.; Dahari, S. I.; Shamsuddin, M. S.; Rashed, A.; Sarbini, Shahrul Razid (Universiti Putra Malaysia, 2021)
Sago starch which naturally contains high amount of resistant starch, comes to the attention due to its ability to confer health benefits as functional food i.e., prebiotic. The present work aimed to investigate the effects of sago starch consumption on body weight, satiation, caecum short chain fatty acids body, and hepatic lipid content on diet-induced obese rats for obesity management. A total of 36 male Sprague Dawley rats were fat-induced and divided into the obesity-prone and obesity-resistant groups. Eight percent and sixteen percent resistant starch from sago and Hi-maize260 were incorporated into the standardised feed formulation. Food intake was weighed throughout the intervention period. The caecum sample was subjected to short chain fatty acids analysis using HPLC. Hepatic lipid content was measured using the Folch method. Both dosages of sago starch (8 and 16% SRS) promoted body weight loss with a reduction of food intake, which suggested satiety. No significant differences was observed in the production of lactate, acetate, propionate, and butyrate from the caecum sample. Both dosages of sago starch (8 and 16% SRS) also showed lower hepatic lipid content and visceral adipose tissue than the baseline and control groups. However, 8% sago starch showed the lowest hepatic lipid content in obesity-prone and obesity-resistant groups. Overall results demonstrated that sago starch has the potential as an obesity and overweightness control regime as it promotes satiety, lowers visceral adipose tissue, and reduces hepatic lipid content. Consumers should consider adding sago starch in their daily meals.